2013
DOI: 10.3126/jcmc.v3i2.8442
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Histopathological Study of Orbital and Ocular Lesions; a Multicenter Study

Abstract: The study aimed at finding out the morphological and clinico-pathological correlation of Orbital and Ophthalmic lesions in various eye institutes of Nepal. The study also aimed at finding out the prevalence of Ophthalmic lesions needing histo­pathological examination. This cross sectional descriptive study was carried out in various tertiary eye hospitals of Nepal from 2008 – 2012. The department of pathology was also incorporated in giving the correct histopathological findings in time. All the relevant data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
27
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 3 publications
13
27
4
Order By: Relevance
“…[7][8][9][10] Both benign and malignant lesions of the eyelid and orbital tumors were most commonly seen in patients in the age group 30-40 years. It is in concordance with a study conducted by P Bastola et al 11 In our study, benign lesions were 58.73% while malignant lesions were 41.27%, while study conducted by Ud Din N et al 12 was quite similar to the present study, in which the benign and malignant lesions were found to be 61.5% and 38.5% respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[7][8][9][10] Both benign and malignant lesions of the eyelid and orbital tumors were most commonly seen in patients in the age group 30-40 years. It is in concordance with a study conducted by P Bastola et al 11 In our study, benign lesions were 58.73% while malignant lesions were 41.27%, while study conducted by Ud Din N et al 12 was quite similar to the present study, in which the benign and malignant lesions were found to be 61.5% and 38.5% respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In a similar study conducted by Bastola et al Non-Hodgkin's lymphoma was commonest followed by rhabdomyosarcoma. 11 Most common malignant tumour of the lacrimal gland in the present study was found to be adenoid cystic carcinoma (ACC) which is in concordance with the literature as ACC comprises of about 25-30% of epithelial tumours of the lacrimal gland. 15 Like Ud-Din N et al study, most common malignancy in children in present study was also retinoblastoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bastola et al found that most common benign lesions were granuloma pyogenicum(22.5%) followed by intradermal nevus (4.5%). In our study most common malignant lesion seen was squamous intraepithelial neoplasia consistent with other studies 12,13,14 . For the Orbital Tumours we studied we identified benign Tumours in 7 cases and malignant Tumour in 1 case.…”
Section: Discussionsupporting
confidence: 81%
“…Zaidi N et al found that benign Tumours were more frequent which were seen in 74.50% of all cases studied and malignant Tumours were seen in 25.50% 14 . Another study conducted by Bastola et al also found that benign lesions were more common which were seen in 79% of all cases studied and malignant lesions were seen in 21% 13 . In our study Benign lesions were represented by Nevus (4 cases), followed by dermolipoma (2 cases), papilloma (1 case) and dermoid cyst (1 case).…”
Section: Discussionmentioning
confidence: 94%